2022
DOI: 10.3390/cimb44050136
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Microbiome in Gastroentero-Pancreatic Neuroendocrine Neoplasms (GEP-NENs)

Abstract: Gut microbiome balance plays a key role in human health and maintains gut barrier integrity. Dysbiosis, referring to impaired gut microbiome, is linked to a variety of diseases, including cancers, through modulation of the inflammatory process. Most studies concentrated on adenocarcinoma of different sites with very limited information on gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs). In this study, we have analyzed the gut microbiome (both fungal and bacterial communities) in patients with metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Eggerthella is part of the normal human intestinal microbiome and has been most commonly associated with infections spreading from the gastrointestinal tract 60 , but it has also been found interacting with food intake while influencing metabolism of drugs 61 . This genus has also been shown to be more abundant in individuals with psychiatric diseases 62 and higher grade neoplasms 63 . E. lenta from the same genus correlates with taurodeoxycholic acid, a bile acid metabolite, in the colon of smoke-exposed mice 64 and has increased abundance in the presence of blood in stool, which is a marker for CRC 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Eggerthella is part of the normal human intestinal microbiome and has been most commonly associated with infections spreading from the gastrointestinal tract 60 , but it has also been found interacting with food intake while influencing metabolism of drugs 61 . This genus has also been shown to be more abundant in individuals with psychiatric diseases 62 and higher grade neoplasms 63 . E. lenta from the same genus correlates with taurodeoxycholic acid, a bile acid metabolite, in the colon of smoke-exposed mice 64 and has increased abundance in the presence of blood in stool, which is a marker for CRC 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine tumor (NET) is a heterogeneous group of tumors originating from different neuroendocrine organs or cells (108). In addition to PitNETs, the NETs in other organs have also been linked to gut microbes (109). By studying stool samples from 18 patients with rectal neuroendocrine tumor (RNET) and 40 controls, Hu et al found that patients with RNET had aberrant depletion and attenuated connection.…”
Section: Gut Microbes and Other Neuroendocrine Tumorsmentioning
confidence: 99%
“…To reduce batch effect, all samples were stored at −20 • C, then processed and analyzed concurrently for microbial composition. The methodology, including DNA extraction, PCR amplification, library preparation, and sequencing, is detailed in Appendix A and was previously reported by our lab [79,80]. Library sequencing was completed on an Ion Torrent S5 sequencer (ThermoFisher Scientific,.…”
Section: Sample Collection and Processingmentioning
confidence: 99%